Dichorisandra rhizantha (Commelinaceae), a new morphologically unusual species from Bahia, Brazil - Aona, Lidyanne Y. S.; de Souza, Everton Hilo; de Almeida Júnior, Railson A. C.; Marinho, Lucas C.; Bittrich, Volker; Amaral, Maria Do Carmo E. Do (Phytotaxa, 2022)
We describe, discuss, and illustrate Dichorisandra rhizantha, a new species from a transitional area between the Atlantic Forest and Caatinga domains in eastern Bahia state, Brazil. The species was assessed as Endangered, especially for its distribution restricted to forest fragments. The new species is morphologically similar to D. hirtella, D. radicalis and D. jardimii, but clearly differs from these by the inflorescence arising directly from the rhizome, and a pubescent indument on stem, leaves and sepals. We also present a distribution map of the species and taxonomic comments.